2019
DOI: 10.1016/j.neuroimage.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mesoscopic properties of deep gray matter iron through a model-based simultaneous analysis of magnetic susceptibility and R2* - A pilot study in patients with multiple sclerosis and normal controls

Abstract: Most studies of brain iron relied on the effect of the iron on magnetic resonance (MR) relaxation properties, such as R 2 * , and bulk tissue magnetic susceptibility, as measured by quantitative susceptibility mapping (QSM). The present study exploited the dependence of R 2 * and magnetic susceptibility on physical interactions at different length-scales to retrieve information about the tissue microenvironment, rather than the iron concentration. We introduce a method for the simultaneous analysis of brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…These dependencies lead to variations across studies in terms of the accuracy of measured susceptibilities. Another limitation of QSM is the surface artifacts (arising from strong susceptibility gradient at tissue interfaces, such as at the brain surfaces or around the blood vessels) and streaking artifacts (due to noise and mathematical limitations in solving the point-dipole problem) (Deistung et al, 2017 ; Taege et al, 2019 ; Jung et al, 2020 ). The third factor that contributes to the heterogeneity of susceptibility measurements across sites and studies is the inconsistent reference regions considered for relative measurement of magnetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dependencies lead to variations across studies in terms of the accuracy of measured susceptibilities. Another limitation of QSM is the surface artifacts (arising from strong susceptibility gradient at tissue interfaces, such as at the brain surfaces or around the blood vessels) and streaking artifacts (due to noise and mathematical limitations in solving the point-dipole problem) (Deistung et al, 2017 ; Taege et al, 2019 ; Jung et al, 2020 ). The third factor that contributes to the heterogeneity of susceptibility measurements across sites and studies is the inconsistent reference regions considered for relative measurement of magnetic susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the possible effect of atrophy in measurements of mean susceptibility should not be overlooked. It has been suggested that atrophy of a ROI may result in higher iron concentration and therefore mean susceptibility in the absence of a change in absolute iron content (Taege et al, 2019 ). To account for and further explore this possibility, studies should consider the effect of atrophy as a confounder in magnetic susceptibility comparisons in their statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This schematic does not include scenarios in which iron influx occurs, or iron is removed from iron‐containing cells (see Table 3). The schematic also does not include scenarios in which iron is transferred between cell‐types (e.g., released by iron‐containing cells and then taken up by iron‐free cells) because such an iron transfer would not affect the bulk tissue magnetic susceptibility (Taege et al, 2019). Furthermore, the conclusions about changes in iron concentration and content would be similar if the “iron‐free” cells in the schematic were not completely iron‐free but contained considerably less iron than the “iron‐containing” cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, R2* mapping is sensitive to tissue differences in tissue susceptibility distribution. Incorporating measures from both QSM and R2* mapping has the potential to assess iron related changes in the brain, especially in the deep gray matter with high vasculature ( 170 ).…”
Section: Discussionmentioning
confidence: 99%